From Geographic information systems to Spatial data infrastructures a global perspective - Masser, Ian (Boca Raton : CRC Press, 2019)
This book draws on author's wealth of knowledge working on numerous projects across many countries. It provides a clear overview of the development of the SDI concept and SDI worldwide implementation and brings a logical chronological approach to the linkage of GIS technology with SDI enabling data. The theory and practice approach help understand that SDI development and implementation is very much a social process of learning by doing. The author masterfully selects main historical developments and updates them with an analytical perspective promoting informed and responsible use of geographic information and geospatial technologies for the benefit of society from local to global scales. Features Subject matter spans thirty years of the development of GIS and SDI. Brings a social science perspective into GIS and SDI debates that have been largely dominated by technical considerations. Based on a world-wide perspective as a result of the author's experience and research in the USA, Australia, Canada, Brazil, Peru, China, India, Korea, Malaysia, and Japan as well as most European countries. Draws upon professional and academic experience relating to pioneering UK and European GIS research initiatives. Includes updated historical material with an analytical perspective explaining what was done right, and what didn't work.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Database Management / Data Mining; SCIENCE / Earth Sciences / General; TECHNOLOGY / Remote Sensing; Geographic information systems; Spatial data infrastructures